4.7y-3.7y+6.1=-9.2-3.2

Subtract 3.7y from 4.7y.

y+6.1=-9.2-3.2

Subtract 3.2 from -9.2.

y+6.1=-12.4

Subtract 6.1 from both sides of the equation.

y=-12.4-6.1

Subtract 6.1 from -12.4.

y=-18.5

y=-18.5

Solve for y 4.7y-3.7y+6.1=-9.2-3.2

Skip to content
# Solve for y 4.7y-3.7y+6.1=-9.2-3.2

4.7y-3.7y+6.1=-9.2-3.2

Subtract 3.7y from 4.7y.

y+6.1=-9.2-3.2

Subtract 3.2 from -9.2.

y+6.1=-12.4

Subtract 6.1 from both sides of the equation.

y=-12.4-6.1

Subtract 6.1 from -12.4.

y=-18.5

y=-18.5

Solve for y 4.7y-3.7y+6.1=-9.2-3.2